Two moments in the recent history of biblical reading: the Bible as literature from Erich Auerbach and Robert Alter - Anderson de Oliveira Lima (Teoliterária: Revista Brasileira de Literaturas e Teologias, 2015)
This article is dedicated to the understanding of what is read the Bible as literature. We present two moments in the recent history of Bible reading that seem crucial to the definition of this form of reading. The two moments were the publications of two important works that approached the biblical texts from a literary perspective, differing from traditional approaches, religious and exegetical, and influencing the next generations. The first of these two works was Mimesis: The Representation of Reality in Western Literature by Erich Auerbach, originally published in 1946, the other was The Art of Biblical Narrative by Robert Alter, original 1981. We examine some of the main contributions of these two authors for the Bible studies and try to demonstrate that there is a thematic dependence between their works, then list the main assumptions of this way of reading the Bible today, and defend the hypothesis that religious mediation still dividing the Bible studies.